Analisis Jarak Kandang Ayam Potong Dengan Tingkat Kepadatan Lalat Di Rumah Penduduk Desa Rajabasa Baru Kecamatan Mataram Baru Kabupaten Lampung Timur - Adelia Putri; Helina Helmy (Inovasi Kesehatan Global, 2024)
One indicator of inadequate environmental cleanliness is fly density; Higher fly densities correspond to higher fly populations in the area. Fly handling is necessary immediately because of the potential health risks associated with fly density. The aim of this study is to quantify the distance between the fly density in local homes and the slaughter chicken cages in Rajabasa Baru Village, Mataram Baru Subdistrict, East Lampung Regency. The study used a qualitative descriptive technique. The dwellings around the slaughter chicken coop are the subject of this study, which is being conducted in Rajabasa Baru Village, Mataram Baru Subdistrict, East Lampung Regency. Observation and documentation are the methods employed to gather data for this study. The results of the research found that the distance that had the highest density of flies was 150 meters with an average of 24 individuals, while at a distance of 450 meters there were only 28 individuals, then at a distance of 900 meters only 13 individuals. Fly density tends to decrease with increasing distance from the source, namely the chicken drum. However, the density of flies is still quite significant even at greater distances, indicating the importance of managing and controlling fly populations around these areas to maintain environmental health and prevent the spread of disease.